2013
DOI: 10.3810/pgm.2013.03.2640
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Patients With Irritable Bowel Syndrome With Constipation or Chronic Idiopathic Constipation: A Review of the Literature From the Past Decade

Abstract: Patients with IBS-C or CIC frequently experience a wide range of comorbidities that contribute to their disease burden. Thus, we believe that medical professionals should consider common comorbidities when diagnosing and treating patients with IBS-C or CIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 59 publications
3
41
0
1
Order By: Relevance
“…The prevalence of anxiety and depression in DD patients was much higher than the rates in the general population. These findings are consistent with previous literature that has documented a positive association-though not a causal relationship-between certain psychological disorders and DD [37,38]. We found that DD patients also have lower quality of life than the general population.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of anxiety and depression in DD patients was much higher than the rates in the general population. These findings are consistent with previous literature that has documented a positive association-though not a causal relationship-between certain psychological disorders and DD [37,38]. We found that DD patients also have lower quality of life than the general population.…”
Section: Discussionsupporting
confidence: 83%
“…Patients suffering from comorbid conditions like diabetes, hypothyroidism, hypertension and cardiovascular, neurological, GI and other metabolic disorders frequently experience constipation due to disordered colonic and/or pelvic floor/anorectal function 37 . In the present study, higher proportion of FC patients had a history of hypertension (16%) and diabetes (10.2%); resulting in higher utilization of antihypertensive and antidiabetic medications, further leading to lower frequency of bowel movements.…”
Section: Discussionmentioning
confidence: 99%
“…21,39 In another study, dyspepsia and diabetes were reported as the most common comorbidities in patients with IBS-C and FC, respectively. 37 In addition, 7.15% patients of FC were on antidepressants for management of stress/ anxiety/ depression. Literature review reports that anxiety/depression is the independent risk factors for constipation.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review which analyzed 35 studies about comorbid conditions in IBS-C and chronic idiopathic constipation, FD and depression were reported as the most common comorbid diseases in patients with IBS-C, whereas FD, DM, and depression were the most commonly overlapping diseases in patients with chronic idiopathic constipation. 31 In another web-based, crosssectional study conducted in the United States, the impact of overlapping FD, GERD, IBS-C, and FC on symptom burden and consulting behavior was assessed. 32 Of the 2641 responders, 328 and 552 persons met the Rome III criteria for IBS-C or FC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is not difficult to predict that the quality of life will be lower with more severe symptoms in the overlapping groups, and there are several reports on this. 3,5,6,31 In this study, we assessed both constipation-associated QOL and general health-related QOL with PAC-QOL and EQ-5D-3L questionnaires, respectively. PAC-QOL questionnaire contains 28 items assigned to 4 domains: worries and concerns (11 items), physical discomfort (4 items), psychosocial discomfort (8 items), and satisfaction (5 items).…”
Section: Discussionmentioning
confidence: 99%